1971
DOI: 10.1073/pnas.68.8.1815
|View full text |Cite
|
Sign up to set email alerts
|

Proteins from Plant Cell Walls Inhibit Polygalacturonases Secreted by Plant Pathogens

Abstract: Proteins extracted from the cell walls of Red Kidney bean hypocotyls, tomato stems, and suspension-cultured sycamore cells can completely inhibit the activity of the polygalacturonases (polygalaicturonide hydrolases, EC 3.2.1.15) secreted by the fungal plant pathogens Colletotrichum lindemuthianum, Fusarium oxysporum, and Sclerotium rolfsii. The inhibitor of the C. lindemuthianum polygalacturonase, purified 560-fold from bean hypocotyl extracts, is 40 times as effective an inhibitor of the C. lindemuthianum po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
0
3

Year Published

1973
1973
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(72 citation statements)
references
References 27 publications
2
67
0
3
Order By: Relevance
“…Selected protease inhibitors were ineffective in inhibiting PGIP activity (Table II). All these results strongly suggested that the PGIP we have purified is likely to be the same protein characterized by other authors (3,28).…”
supporting
confidence: 62%
“…Selected protease inhibitors were ineffective in inhibiting PGIP activity (Table II). All these results strongly suggested that the PGIP we have purified is likely to be the same protein characterized by other authors (3,28).…”
supporting
confidence: 62%
“…between 10 and 15 are potent elicitors of plant defense responses, but are only transiently produced by the action of EPG in vitro. A polygalacturonase-inhibiting protein (PGIP) has been found to be present in the cell walls of all dicotyledonous plants that have been examined (Albersheim and Anderson, 1971;Cervone et a/., 1986;. In vjtro experiments have demonstrated that addition of PGlP to fungal EPG in the presence of polygalacturonic acid results in the prolonged existence in the reaction mixture of elicitor-active oligogalacturonides (d.p.s.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, fungal and bacterial pathogens are armed with a deconstructing mixture of enzymes that depolymerize polysaccharides in the plant cell wall (1). At the same time, plants can secrete proteins that inhibit these degradative glycosidases, including polygalacturonase-inhibitor proteins (2), pectin lyase inhibitor proteins (3), and two different classes of endoxylanase inhibitors (4,5).…”
mentioning
confidence: 99%